IMPROVING READING COMPREHENSION THROUGH SEMANTIC MAPPING STRATEGY FOR INDONESIAN SENIOR HIGH SCHOOL STUDENTS - Adelia Puspa; Syahrial . (Universitas Bengkulu, 2016)
This research investigates how semantic mapping strategy can improve students’ reading comprehension. The subject of this research was the ten grade students consisted of 32 students. In this classroom action research, the researcher used quantitative data to see the improvement of the students’ reading comprehension, and qualitative data to explain the change in students’ behaviour during the implementation of the strategy. Based on the result of the test conducted at the end of the cycle and the analysis of the observation checklist and field notes, it could be concluded that both the students’ reading comprehension and the students’ attitude during the reading class have been improved. The students who passed the test improved from 43.75% at the baseline data to 87.5% at the end of cycle II. This improvement mostly influenced by the second and the third phase of semantic mapping strategy, which are brainstorming categorization. In this phases, the students activate their prior know and learn to visualize relationship between ideas and put them into categories. Thus, the students have a better comprehension of the text. The students also showed better motivation, interest, participation, and enthusiasm toward the learning process proven by the results of the observation. However, the materials in this present research were short reading texts. The implementation of the strategy on longer reading texts should be taken into a deeper study in the future research.